Cost and Time Efficiency Analysis on Latei Beams and Wall Work: Case Study Of GLT4 And GKU2 Projects at Sumatra Institute of Technology - Isnaeni Aprilia; Darmawan Pontan (Publikasi Indonesia, 2023)
Engineering Laboratory Building Project 4 (GLT4) and Public Lecture Building (GKU2) at the Sumatra Institute of Technology, South Lampung is part of the construction of a lecture building where this development aims to facilitate and provide comfortable learning infrastructure for all students. This study evaluates the cost of latei beams and walls. The method used is to calculate the cost of implementation and time evaluation so as to change the conventional implementation method to precast / precast through the Cost and Time Evaluation Method. The research objective was to determine the cost efficiency between the conventional method and the precast method for beam and wall work. Types of qualitative research use cost and time evaluation method is one of the well-known methods and has a considerable potential for success in controlling costs and time. This technique uses an analysis approach to its function. The process carried out is to reduce costs as much as possible while still paying attention to the desired quality and reliability. The results of this study indicate that in the Construction of the Engineering Laboratory Building (GLT) 4 and General Lecture Building (GKU) 2 projects for latei beam work it was found that the cost of latei beam work had a profit of 24% with a value of Rp. 95,090,232 and has an efficiency of 6% with a value of Rp. 25,145,911. The amount of efficiency occurs due to changes in material use, reducing wages and material costs by negotiating with suppliers. Wall work has an efficiency of 11% or Rp. 309,214,847 and has a profit of 20% or Rp. 686,542,006. Efficiency occurs by reducing wages and material costs by negotiating with suppliers.